Lifestyle enrichment through social and cognitive engagement in later life: its associations with frailty trajectories and risk over 11 years - Claire McCubbin; Joanne Ryan; Zimu Wu; Swarna Vishwanath; Alice J. Owen; Sara E. Espinoza; Robyn L. Woods; Aung Zaw Zaw Phyo (GeroScience, 2026)
Frailty is a common geriatric syndrome associated with higher risks of hospitalisation and falls. The extent to which social and cognitive engagement activities (lifestyle enrichment) influence frailty is still largely unexplored. This study investigates the association between such enrichment and changes in frailty and frailty risk; 12,862 community-dwelling Australians aged ≥70 (54.4% female) enrolled in the ASPREE study were followed for 11 years. Nineteen baseline measures of social and cognitive activity (lifestyle enrichment) were grouped into seven domains using exploratory-factor analysis. Frailty was assessed annually over 11 years using a 67-item Frailty Index (FI) and modified Fried phenotype. Linear mixed models and Cox regression were used. Frequent passive mental activities (e.g., reading, watching TV) or adult literacy (e.g., writing letters, computer use) were associated with a 0.04-unit slower increase in FI-defined frailty burden. External outings had a 0.03-unit reduction annually; interpersonal networks or social activities, 0.02; and creative artistic engagement, 0.01. Active mental engagement showed no significant change. Over a median of 7.38-year follow-up, 3630 participants had an incident frailty. Passive mental engagement, interpersonal networks, social activities, external outings, adult literacy, and active mental engagement were associated with 2% to 5% lower risk of frailty. These associations were more evident among women and individuals with middle-/high-socioeconomic status. Similar findings were observed when using Fried phenotype. Frequent social and cognitive activities were associated with slower frailty progression and reduced frailty risk, informing clinical and public health strategies to maintain older adults’ independence and resilience. Graphical abstract